27.0k views
5 votes
Multiply the polynomial by distribution. Show your work and explain the steps you used to solve.

(a – 3)(a2 + 2a – 6)



help please

User Barremian
by
4.8k points

1 Answer

2 votes

Hello,

Why "Multiply the polynomial by distribution" ?

It's s t u p i d, you compliquate the equation.

In order to find the roots of P(a)=(a-3)(a²+2a-6)=0

a²+2a-6

=(a²+2a+1)-7

=(a+1)²-7

=(a-√7)(a+√7)

P(a)=(a-3)(a-√7)(a+√7)

Roots are 3,√7 and -√7

(If i have well understood the question , sorry if not)

User Mark Meeus
by
5.9k points